Model of Holistic Parents' Participation in Children's Education in the Hostel - Nur Cholidah; Sigit Haryanto; Dwi Maryani; Febriyani Sulistyaningsih; Djalal Fuadi (CV. Creative Tugu Pena, 2024)
This review means to evaluate the meaning of parental help inside the setting of Islamic life experience schools (pondok pesantren) and investigate different models of help that can be applied. The examination approach utilized in this study is an exhaustive survey of existing writing (Library Exploration). The discoveries of this study show the significant job of parental help inside the pondok pesantren climate in working with the advancement of the understudies (santri). In such manner, a few models of help can be carried out, including profound, social, financial, and participatory help. Each model of help assumes an unmistakable part in supporting santri to accomplish worked on scholastic execution and advance positive self-awareness. The effect of parental help on santri is exceptionally huge, with understudies who get sufficient help having a tendency to have more significant levels of satisfaction and more grounded inspiration for learning. This help additionally helps santri conquer different difficulties and snags that might emerge during their visit in the pesantren. Moreover, the significance of open correspondence among guardians and santri inside the pesantren can't be put into words. Such correspondence adds to the production of a climate that upholds the comprehensive improvement of santri. Powerful correspondence permits guardians to all the more likely comprehend the necessities of their kids and helps santri feel more good in the pesantren climate.